Association of Hypothermia in Newborn at Admission with Morbidity and Mortality in a Tertiary Level Hospital in Bangladesh (Bangladesh Journal of Child Health, 2025)
Background: The neonatal mortality is still significantly high in Bangladesh. One of the major risk factors for morbidity and mortality in the first 28 days of life is neonatal hypothermia. Hypothermia is a risk factor for neonatal sepsis, intraventricular haemorrhage, necrotizing enterocolitis, respiratory distress, hypoglycemia, metabolic acidosis, hyperbilirubinemia, scleroderma, DIC and pulmonary haemorrhage. Objective: To find out the association between neonatal hypothermia at admission with mortality and morbidity. Methodology: This prospective observational study was conducted in Department of Neonatology in Bangabandhu Sheikh Mujib Medical University over a period of one year from July 2021 to June 2022. Temperature was measured in axilla using commercially available Digital Axillary Thermometer (Elite Digital Thermometer). Study population was divided into normothermic (84) and hypothermic (84) group. The babies were followed up until discharge or death, whichever came first. The primary outcome in this study was neonatal mortality and morbidity. Results: Among the total study population of 497 newborns, frequency of hypothermia was 18.90%. Outborn babies significantly suffered from hypothermia (p=0.021). Early Onset Neonatal Sepsis, Late Onset Neonatal sepsis, shock and hospital stay were significantly higher in hypothermic group than normothermic group (p= 0.03,